Chemistry and Pharmacological Actions of Delphinidin, a Dietary Purple Pigment in Anthocyanidin and Anthocyanin Forms - Husain, Asif; Chanana, Harshit; Khan, Shah Alam; Dhanalekshmi, U. M.; Ali, M.; Alghamdi, Anwar A.; Ahmad, Aftab (Frontiers in Nutrition, 2022)
Anthocyanins are naturally occurring water-soluble flavonoids abundantly present in the fruits and vegetables. The anthocyanins are polymethoxy derivatives of 2-phenyl-benzopyrylium or flavylium salts. Delphinidin (Dp) is a purple-colored plant pigment, which occurs in a variety of berries, eggplant, roselle and wine. Dp is found in a variety of glycosidic forms ranging from glucoside to arabinoside. Dp is highly active in its aglycone form, but the presence of sugar moiety is vital for its bioavailability. Several animal and human clinical studies have shown it exert the beneficial effects on the gut microbiota. Dp exhibits a variety of useful biological activities by distinct and complex mechanisms. This manuscript highlights the basic characteristics, chemistry, biosynthesis, stability profiling, chemical-synthesis, physicochemical parameters along with various analytical methods developed for extraction, isolation and characterization, diverse biological activities and granted patents to this lead anthocyanin molecule, Dp. This review aims to open pathways for further exploration and research investigation into the true potential of the naturally occurring purple pigment (Dp) in its Anthocyanidin and Anthocyanin forms beyond nutrition.